Culex quinquefasciatus larvae development arrested when fed on Neochloris aquatica - Gil, M. Florencia; Fassolari, Marisol; Battaglia, Marina E.; Berón, Corina M. (PLOS Neglected Tropical Diseases, 2021)
Author summary Culex quinquefasciatus, known as a southern house mosquito, is a domestic and cosmopolitan species widely distributed in the tropical and subtropical regions of the Americas, Asia, Africa, and Oceania. It is strongly associated with humans and other vertebrates, and it has been given a relevant role in the transmission of arboviruses and parasitic diseases, some of them very important in veterinary and human health. Adult females feed mainly on birds, although they can also feed on humans and other mammals, being effective not only in surviving in the environment, but in vectoring pathogens as well. In addition, Culex pipiens and Cx. quinquefasciatus, members of the Cx. pipiens complex, coexist in a distribution hybrid zone and their mating produces viable offspring, expanding its distribution even more. Moreover, larvae can be developed in different environments, including standing water generated by humans and livestock, being able to exploit food sources found in them. This ability to get adapted to different conditions make it a successful host with great potential to initiate and facilitate the transmission of pathogens, therefore it is essential to develop environmentally friendly control systems that can be used in integrated vector management programs. In this context, the use of microorganisms, like microalgae, with the capability to alter or slow down the development of insects such as Cx. quinquefasciatus must be exhaustively explored.